Scientific literacy of teachers from the 4th and 5th grades of Elementary School: A literature review on the use of the internet as a source of information to support scientific research in science education (Research, Society and Development, 2021)
The present study aims to map the existing research on  scientific literacy of teachers of 4th and 5th years  of elementary school, with the use of  internet as a source of information to support scientific research in science education.  This is descriptive and qualitative research. A survey was carried out in the following bibliographic resources: articles, dissertations and theses published between 2007 and 2019, this search was carried out in five databases, namely: CAPES Journal Portal, Scientific Electronic Library Online (SCIELO), Digital Thesis Library and Dissertations, Sucupira Platform and Magazines Classified by CAPES - QUALIS in the Education área. We  used as a research tool the simple search with the following terms accompanied by quotation marks: "Alfabetização científica", "Scientific Literacy", "Elementary school teachers", "Internet", "School research", "Bibliographic research", “Scientific research”. We also utilized search, with, the boolean operator AND to delimit the research, equating the expression with all the words, by means of terms: Alfabetização científica and Elementary school teachers, Alfabetização científca and Internet, Alfabetização científica and school research, Alfabetização científica and bibliographic research, Alfabetização científica and Scientific research, Cientific Literacy and Elementary School Teachers, Scientific Literacy and Internet, Scientific Literacy and School research, Scientific Literacy and Bibliographic research, Scientific Literacy  and Scientific research. By  analyzing  the titles, abstracts and the content of the articles, we have as a result some approximations to the theme and the objective of the thesis, however these do not meet the informational needs to property answer  the problem raised.